Coastal Community Perceptions of Waste Management as an Effort to Maintain Marine Sustainability in Tapanuli Tengah Regency, North Sumatera - Harahap, Husnul Yaqin; Mahaji, Toga; Siburian, Juliana Pebrina; Anugerah, Tirta; Adiprayoga, Shofian Nanda (International Journal of Marine Engineering Innovation and Research, 2025)
This study aims to determine the perception of coastal communities in Central Tapanuli towards waste management as an effort to maintain marine sustainability and formulate waste utilization activities as an effort to increase the income of coastal communities in Central Tapanuli. The research method used in this study is a mixed research method. This study was conducted in three locations, namely in Lubuk Tukko Baru Village and Muara Nibung Village, Pandan District and in Jago Jago Village, Badiri District with a total of 100 respondents in the study. Based on the results of the study, the results of the perception of "community understanding of waste management in coastal areas" were obtained with an overall average value of 91.16%, meaning that all respondents strongly agreed or understood very well. Then for the results of the perception of "understanding of coastal environmental cleanliness and waste utilization to increase family income" the overall average result was 53%, with the category sometimes or less understanding. Then the results of several activities were obtained that were appropriate for coastal communities in Central Tapanuli Regency in utilizing waste as an effort to increase income with the management categories divided between organic waste and non-organic waste. Organic waste is very possible to be used for maggot cultivation activities or commonly called Black Soldier Fly (BSF) maggots and making candles and soap for households from used cooking oil. Then for non-organic waste, it is very possible to carry out activities to form a Waste Bank, establish a skills center that provides economic added value, and implement cooperation with private and government companies in managing non-organic waste.